The Relationship among Islamic Law and Customary Law: A Study on Wedding Processions in Kuntu Village - ZIkri, Ahmad (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
Islamic law affects the legal style in Indonesia. This is because the majority of the Indonesian population adheres to Islam. Islamic values enter the joints of people's lives. This study aims to analyze the traditional wedding procession in Kuntu Village about Islamic law and whether it is appropriate or contradictory. The method used in this study is qualitative research. This research was conducted in Kuntu Village, Kampar Kiri District, Kampar Regency, Riau Province. The information collected in this study is related to the harmony of customary law and Islamic law at weddings in Kuntu Village, which begins by looking at how the wedding procession is carried out in Kuntu Village and seeing how customary law and Islamic law run. This study concludes that customary law and Islamic law in the procession of traditional wedding events in Kuntu Village go hand in hand. The people of Kuntu Village give the motto that the custom of besandi syara', syara' besandi kitabullah.